Estimación Porcentual de Incidencia de Problemas estructurales originados por errores en el diseño y construcción de instalaciones hidrosanitarias en Colta - Cargua Pilco, Belén Estefanía (2022)
Population growth has increased the demand for housing in the canton of Colta, causing an increase in informal construction and disorganized growth. Most of the buildings are constructed by unskilled labor (mingas, laborers, bricklayers and master builders), with empirically acquired knowledge of construction techniques, but which leave aside important aspects that can cause future problems. In this research, the incidence of structural problems caused by errors in the design and construction of plumbing installations in buildings located in the urban area of Colta canton with residential, commercial and/or mixed land use was estimated as a percentage. A mixed type of research was used (quantitative and qualitative) with a purely field data collection. Using ArcGIS software version 10.5, it was found that 36.60% of the properties are affected by the problem and were identified as "Affected", identifying in these buildings problems such as: beams crossed by pipes inside and outside the confinement zone, pipes embedded in columns, and beams crossed by two or more pipes at the same point outside and inside the confinement zone. Those buildings that do not present the problem were identified as "Not affected" and those buildings that could not be inspected as "N/A